2018
DOI: 10.1038/s41526-017-0038-4
|View full text |Cite
|
Sign up to set email alerts
|

Gene-metabolite profile integration to understand the cause of spaceflight induced immunodeficiency

Abstract: Spaceflight presents a spectrum of stresses very different from those associated with terrestrial conditions. Our previous study (BMC Genom. 15: 659, 2014) integrated the expressions of mRNAs, microRNAs, and proteins and results indicated that microgravity induces an immunosuppressive state that can facilitate opportunistic pathogenic attack. However, the existing data are not sufficient for elucidating the molecular drivers of the given immunosuppressed state. To meet this knowledge gap, we focused on the met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 73 publications
2
18
0
Order By: Relevance
“…To assess if exposure of ECs to space microgravity has a significant impact on cell energy metabolism, we quantified the glucose ( Figure 3A ) and L -lactate ( Figure 3B ) concentrations from the cell culture supernatants. Compared with ground control, the glucose concentration increased additional 129% ( Figure 3A ) and the L -lactate concentration was reduced to 16% ( Figure 3B ) for EA.hy926 cells cultured for 3 days in space, implying a suppressed metabolism with lower glucose consumption and lactate production in agreement with previous study ( Chakraborty et al, 2018 ). The significant difference disappeared between the cells cultured for 10 days in space and on ground ( Figure 3 ), probably due to the slowed growth associated with contact inhibition in long-term space culture.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…To assess if exposure of ECs to space microgravity has a significant impact on cell energy metabolism, we quantified the glucose ( Figure 3A ) and L -lactate ( Figure 3B ) concentrations from the cell culture supernatants. Compared with ground control, the glucose concentration increased additional 129% ( Figure 3A ) and the L -lactate concentration was reduced to 16% ( Figure 3B ) for EA.hy926 cells cultured for 3 days in space, implying a suppressed metabolism with lower glucose consumption and lactate production in agreement with previous study ( Chakraborty et al, 2018 ). The significant difference disappeared between the cells cultured for 10 days in space and on ground ( Figure 3 ), probably due to the slowed growth associated with contact inhibition in long-term space culture.…”
Section: Resultssupporting
confidence: 91%
“…ECs are highly sensitive to mechanical forces such as fluid shear stress, cyclic tensile strain and substrate stiffness, and contribute to cardiovascular deconditioning and immune dysfunction faced by astronauts upon the removal of gravitational forces during spaceflight ( Byfield et al, 2009 ; Chancellor et al, 2010 ; Maier et al, 2015 ). Exposure to microgravity in space can induce the morphological and gene expression changes in ECs, displaying the heterogeneity of cell size and shape ( Kapitonova et al, 2012 ), three-dimensional growth ( Pietsch et al, 2017 ), energy and protein metabolism deficiency ( Chakraborty et al, 2018 ), significant suppression of genes associated with host defense ( Chakraborty et al, 2014 ), and alterations in genes involved in cell adhesion, oxidative phosphorylation, and stress responses ( Versari et al, 2013 ). To date, only a few relevant studies in space have been reported and the impact of real microgravity on EC functions is still unclear mainly due to the rareness and high costs of spaceflight missions.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies further linked spaceflight to immune deficiencies, metabolic syndrome, bioenergetics dysfunction, and vascular remodeling. (14)(15)(16)(17)(18) Each of these factors individually has shown detrimental effects on musculoskeletal health; in this perspective, this Rodent Research 4 (RR4) project presented us a unique opportunity to investigate the cumulative effects of all of these stress factors on muscle fitness. Our previous studies (11,19) showed that femoral and tibial trabecular bone volume was significantly reduced during spaceflight.…”
Section: Discussionmentioning
confidence: 99%
“…In either case, it is also notable that our data on the immune functions in spaceflight correlated well with previous works that have associated these immunodeficiencies to energy deprivation in space. (12,16,46) It is known that oxidative stress and inflammation have a negative impact on muscle health and contribute to sarcopenia, (45,46) and it has been speculated that to mitigate this damage, cells downregulate metabolism and immune functions that typically produce reactive oxygen species. (49) At the background of the rampant negative consequences of spaceflight on healthy rodent quadriceps, there are potentially certain mitigation strategies in effect, again vital information, namely the initiation time of these biofunctions, remained obscure.…”
Section: Discussionmentioning
confidence: 99%
“…Global metabolite mass spectroscopy assay. The metabolite profiling of serum samples was conducted as per the report published previously 32 . Here each sample (5 μL) was injected onto a reverse-phase 50 × 2.1 mm Acquity 1.7-μm C18 column (Waters Corp, Milford, MA) using an Acquity UPLC system (Waters) with a gradient mobile phase consisting of 2% acetonitrile in water containing 0.1% formic acid (Solvent A) and 2% water in acetonitrile containing 0.1% formic acid (Solvent B) and resolved for 10 min at a flow rate of 0.5 mL/min.…”
Section: Methodsmentioning
confidence: 99%